Analysis of the Description of Students' Expectancy with Self-Injurious Behavior - Adhisti Nuur Ainii; Suci Ratna Estria; Etlidawati Etlidawati; Indana Lazulfa (Jurnal Keperawatan Profesional (KEPO), 2026)
Self-harm behavior in adolescents is a common mental health problem and is associated with difficulties in emotion regulation. This study aimed to describe the expectations of students who engage in self-harm behavior. A quantitative method with a descriptive design was employed. The sample consisted of 81 students from “SMP X” who had a history of self-harm behavior and were selected using a purposive sampling technique. Data were collected using the Non-Suicidal Self-Injury Expectancy Questionnaire (NEQ) and analyzed using descriptive statistics. The results showed that expectations related to self-harm behavior were in the high category across several aspects. In the affect regulation aspect, most subjects expected to feel calm after engaging in self-harm behavior (mean = 3.27). In the negative social aspect, subjects expected that others would notice them and perceive them as strange (mean = 3.14). In the communication aspect, subjects expected to receive attention and sympathy from others (mean = 2.99). In the pain aspect, subjects expected self-harm to be painful (mean = 3.27). In the negative self-beliefs aspect, subjects expected to feel ashamed after engaging in self-harm (mean = 3.23). In conclusion, students with a history of self-harm behavior have various expectations, particularly related to emotional regulation and social interaction.